Uji Efektivitas Ekstrak Kulit Apel (Malus sylvestris-mill) Var. Rome Beauty Terhadap Kadar Enzim SGPT Tikus (Rattus norvegicus) Galur Wistar Yang Diinduksi CCL4 (Karbon Tetra Klorida) - Hany Yus; Vina Devi Octaviany; Kristina Simanjuntak (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2017)
Liver is the largest organ in the human body and often injury due to the way of all the materials into the body through the gastrointestinal tract. CCl4 constitute a chemical compound that can induce liver damage. The natural treatment to reduce liver damage can use natural substance that contains antioxidant one of them is apple. When eating an apple people’s habit throw away the peel even though the peel contain high antioxidants. This present study was conducted to determine the effectiveness of apple peel extract var. rome beauty against to level of rat (Rattus norvegicus) SGPT that induced by CCl4. This study used 25 rats (Rattus norvegicus) Wistar strain that were divided into 5 groups randomly. These group are positive control, negative control, apple peel extract var. rome beauty first dose (0.12 mg / kg), the second dose (0.24 mg / kg), and the third dose (0.49 mg / kg). By using one way ANOVA test obtained significant value of alpha 0.000 (P <0.000) that means there are significant differences in effectiveness between the groups. Based on pos hoc test showed the significant differences between the positive control group to the treatment group apple peel extract var. rome beauty first dose, second dose and third dose (P <0.05), meaning that apple peel extract var. rome beauty has effectiveness to SGPT levels. Thus the apple peel extract var.rome beauty has effectiveness to SGPT level of rat that induced by CCl4.